The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1474-8673.1996.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of neurally evoked cholinergic bronchoconstrictor responses by prejunctional NK2 receptors in the guinea‐pig

Abstract: 1. We examined the effect of exogenously administered tachykinins, neurokinin A (NKA), substance P (SP) and neurokinin B (NKB) on neurally mediated cholinergic bronchoconstrictor responses in guinea-pigs. 2. Electrical stimulation of regions in the dorsal medulla oblongata produced a cholinergic bronchospasm that was not affected by depletion of endogenous tachykinins with capsaicin pretreatment (50 mg kg-1, s.c., 1 week earlier) or by pretreatment with the neutral endopeptidase inhibitor, phosphoramidon (3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In addition, this finding raises the possibility of an interaction between e-NANC and cholinergic responses. In fact, it has been already reported that e-NANC neurotransmitters can induce acetylcholine release from postganglionic cholinergic neurons in guinea pig airways (Myers and Undem, 1991;Delaunois et al, 1996;Hey et al, 1996). In our study, this cholinergic component added to the e-NANC response was only manifested after exposure to the highest 0, concentration, since bronchi from non-exposed animals had similar e-NANC responses with or without atropine.…”
Section: Responses To Carbachol Isoproterenol Nitroprusside and Subsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, this finding raises the possibility of an interaction between e-NANC and cholinergic responses. In fact, it has been already reported that e-NANC neurotransmitters can induce acetylcholine release from postganglionic cholinergic neurons in guinea pig airways (Myers and Undem, 1991;Delaunois et al, 1996;Hey et al, 1996). In our study, this cholinergic component added to the e-NANC response was only manifested after exposure to the highest 0, concentration, since bronchi from non-exposed animals had similar e-NANC responses with or without atropine.…”
Section: Responses To Carbachol Isoproterenol Nitroprusside and Subsupporting
confidence: 55%
“…Thus, we were able to measure the e-NANC component with or without atropine incubation ( fig 1C). In fact, it has been already reported that e-NANC neurotransmitters can induce acetylcholine release from postganglionic cholinergic neurons in guinea pig airways (Myers and Undem, 1991;Delaunois et al, 1996;Hey et al, 1996). These results allow us to conclude that 0, introduced a cholinergic component into the second slow contraction produced by EFS (fig 5A), and that the true e-NANC response was unaffected by 0, (fig 5B), as we also found with the concentration-response curves to SP in bronchial preparations.…”
Section: Responses To Carbachol Isoproterenol Nitroprusside and Submentioning
confidence: 99%
“…Catecholamines may inhibit or facilitate acetylcholine overflow through prejunctional a 2 -and b 2 -adrenoceptors, respectively [153][154][155]. Neurokinins such as substance P may enhance cholinergic transmission through facilitatory neurokinin-1 and/or -2 receptors [156,157]. Interestingly, substance P may also induce MBP release from eosinophils, causing M 2 autoreceptor dysfunction, which could act synergistically to direct facilitation [158].…”
Section: Cholinergic Mechanismsmentioning
confidence: 99%
“…Other guinea pigs were given AbNGF 2 days before ozone exposure (which is 3 days before physiological measurements). Other guinea pigs were treated after ozone exposure with either the neurokinin NK 1 receptor antagonist CP-96,345 [3 mg/kg iv (28)] or the NK2 receptor antagonist SR48968 [0.1 mg/kg iv (18)] 30 min before physiological measurements (Fig. 1).…”
Section: Animalsmentioning
confidence: 99%